2001
DOI: 10.1007/s002640000182
|View full text |Cite
|
Sign up to set email alerts
|

Plaster cast compared with bridging external fixation for distal radius fractures of the Colles' type

Abstract: We compared two different treatments for displaced distal radius Colles' type fractures (Older type 3 and 4), at two hospitals. We found bridging external fixation superior to reduction and fixation in a dorsal plaster cast regarding both the end-anatomic results at 3 months and the functional scores at 3 and 9 months (modified Gartland and Werley).Résumé Nous avons effectué dans 2 hôpitaux, une analyse contrôlée de 2 traitements différents des fractures comminutives du radius distal (Older type 3 et 4). Nous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
2
5
0
3
Order By: Relevance
“…Similar results were show by Christensen (2002) and McKenna (2000). [7,8] • Outcome is favourable when injury surgery interval is within 1-3 days.…”
Section: Section: Orthopaedicssupporting
confidence: 83%
“…Similar results were show by Christensen (2002) and McKenna (2000). [7,8] • Outcome is favourable when injury surgery interval is within 1-3 days.…”
Section: Section: Orthopaedicssupporting
confidence: 83%
“…The articular step-off was 0.2 mm (range 0-1) for the ORIF group versus 0.8 mm (range 0-2) for the ex-fix group. The volar tilt averaged 11°(range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for the ORIF group versus 5°(range −3-12) for the ex-fix group (P=0.041). Radial height and inclination were not significantly different between groups.…”
Section: Resultsmentioning
confidence: 99%
“…9 Similar results were found by Kongsholm et al 10 Christensen et al found better results in the EF group but no radial height difference between the groups. 25 Many published series in the literature report results from a wide age range of patients.…”
Section: Discussionmentioning
confidence: 99%